Analytical and Stochastic Modeling Techniques and Applications 19th International Conference, ASMTA 2012, Grenoble, France, June 4-6, 2012. Proceedings - Al-Begain, Khalid; Fiems, Dieter; Vincent, Jean-Marc.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 19th International Conference on Analytical and Stochastic Modelling Techniques and Applications, ASMTA 2012, held in Grenoble, France, in June 2012. The 20 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on queueing systems; networking applications; Markov chains; stochastic modelling.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Software engineering; Computer software; Computer Science; Software Engineering; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl. Internet).; Probability and Statistics in Computer Science; Algorithm Analysis and Problem Complexity